KESETARAAN GENDER DALAM PEMBAHARUAN UNDANG-UNDANG WARIS SOMALIA - Muhammad Salahuddin (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2023)
Inheritance Law which regulates the ownership of assets transferred by the heir to the heirs in the form of money, goods, land or Sharia rights. Reforms regarding inheritance law in Islamic countries on average use 2:1 for the distribution formula, namely men get 2 more shares than women. However, this is not the same as the legal reform that occurred in Somalia, where the division between men and women was equalized, namely 1:1. This research is qualitative research that uses a Gender Equality approach because it sees changes in inheritance law carried out by Somalia to equalize the division between men and women. Somalia's inheritance law is different from the provisions regulated in the Al-Qur'an and the Shafi'i Madzhab which are used as guidelines by the country. Apart from that, the provisions of inheritance law in Somalia are not in accordance with the provisions of other Madzhabs. This shows that the inheritance law has changed due to the social and familial elements that exist in the country of Somalia which adheres to a socialist system. The results of this research, namely the 1:1 distribution formula initiated by Somalia, show that the right to inherit property is equal for men and women. This illustrates that Somalia wants to equalize the rights for men and women in obtaining inheritance. So the issue of gender differences does not determine the distribution of inheritance in Somalia. This equalization of the distribution of inheritance raises the status of women so that equality between men and women is visible.